Modeling of a LiBr-H2O absorption air conditioner system driven by a solar flat plate collector - Bouzyan Lahcen; Toublanc Cyril; Ousegui Abdellah (E3S Web of Conferences, 2023)
In regions with hot and mixed climates, the principal energy users in buildings are the systems that provide cooling and air-conditioning. Buildings consume more energy as a result of their reliance on traditional electrically powered systems. Solar energy has emerged as an important alternative for many uses, including cooling and air-conditioning. In this paper, to simulate a solar-assisted single-stage LiBr-H2O absorption air conditioner system, a mathematical model is presented. The model may simulate either the static or the quasi-static state of the system. The model is constructed using mass and energy balances that are applied to the various components found on the inside of the machine. The experimental data that were acquired for one of the other works in the body of literature are used to validate the model that was developed. In this study, the quantity of energy given by a flat plate solar collector to cool the air in a room in Meknès city on a typical summer day is compared to the cooling load imposed by a cooling fan in the same room. The simulation shows that a flat plate solar collector to power our system can only be used effectively under specific solar irradiance conditions.